Obesidade infantil : a família como unidade promotora da saúde - Saraiva, Klívia Regina de Oliveira (2008)
The family has a leading role in the child health promotion, being the first unity of care that intervenes in the health-sickness process and the is the one that has the greatest influence on the life habits of the child. With regards to feeding, it focus its attention on the quantity of food and not on its quality. The act of feeding the child goes beyond the biologic act, since it is related to the feeding behavior and practices of the family, which are influenced by the historic, social, technological and economic environments. Thus, with the changes in lifestyle of the families, the children can acquire inadequate feeding habits, resulting in child obesity. Starting from this perspective, the study has the goal of understanding the way of life of the families of pre-school age children with obesity risk. For that, it became necessary to use Leininger’s Theory of Diversity and Universality of Cultural Care and the method of Etnonursing, starting by filling an anthropometric evaluation form of 41 children in pre-school age enrolled in two daycares in Fortaleza, where 8 have shown body mass index above the 95 percent (obesity); and by carrying out open interviews with the families of these children during a three-month period, guided by the models Observation-Participation-Reflexion (OPR) and Stranger-Friend. The survey shows that the cultural theme to live with a child with obesity risk: a reality experienced by the families has nuances related with eating is more than satisfying a hunger; being a fat child brings troubles; and family conflicts around a fat child. Therefore, the families believed that feeding the child was a human activity that should be conceded, independently of their socio-economic conditions, of the nutrition value of the food and of the quantity available. The excess weight of the child associated with the stigma of the fat person and to the physical handicaps that it can cause was of little concern to the families, that said it to be characteristic of a child growth phase. The children, being the main target of the care of the family, often were the center of family conflicts, that presented themselves as power disputes between generations and competition between the parents. Faced with these apprehensions, it is understood that the family is the most affective, protective and rewarding universe of the children, being necessary for Nursing to reaches in and involve the remaining contexts – the school and the social ones – in order to develop actions of prevention of child obesity, together with relatives and teachers. That would corroborate the proposal of the Pan-American Organization of Health of creating Health Promotion Schools, starting from a support for the adoption of healthy lifestyles in all contexts of the child’s life.